Amentoflavone Attenuates Clostridium perfringens Gas Gangrene by Targeting Alpha-Toxin and Perfringolysin O - Liu, Shui; Yang, Xiaofeng; Zhang, Hong; Zhang, Jian; Zhou, Yonglin; Wang, Tingting; Hu, Naiyu; Deng, Xuming; Bai, Xiaoxue; Wang, Jianfeng (Frontiers in Pharmacology, 2020)
Clostridium perfringens (C. perfringens) type A strains are the main cause of gas gangrene in humans and animals. Treatment of this lethal disease is limited, and the prognosis is not good. Alpha-toxin (CPA) and perfringolysin O (PFO) secreted by C. perfringens play irreplaceable roles in cytotoxicity to host cells, persistence in host tissues and lethality of gas gangrene pathology. This work determined the influence of amentoflavone, a biflavonoid isolated from Selaginella tamariscina and other plants, on hemolysis and cytotoxicity mediated by CPA and PFO and evaluated the in vivo therapeutic effect on gas gangrene. Our data showed that amentoflavone could block the hemolysis and cytotoxicity induced by CPA and PFO in vitro, thereby mediating significant protection against mortality of infected mice in a mouse gas gangrene model, efficient bacterial clearance in tissues and alleviation of histological damage in vivo. Based on the above results, amentoflavone may be a potential candidate against C. perfringens infection by reducing CPA and PFO-mediated virulence.